Filmes biodegradáveis a base de amido: uma análise acerca da aplicação de diferentes fontes de amido na produção de filmes biodegradáveis utilizando a técnica casting com potencial de utilização em embalagens alimentícias - Reis, Arylson Pereira Santos (2021)
The contemporary world combined with new communication technologies has increased the production of solid waste. Most of these result for many years in the environment, such as the consumption of polymers (plastics) and their consequent inadequate disposal. After searching for various literature, a natural polymer, starch, was found with great potential for the development of biodegradable films (bioplastic) and which can be easily transformed into a thermoplastic material, replacing synthetic polymers. Because it has favorable characteristics for the formation of biodegradable polymers, starch has a relatively low cost and abundant availability, making it possible to produce a polymeric film for use in food packaging. Therefore, materials with a high content of starch, such as corn, potatoes, cassava, pine nuts, among others, may be present in the compostion of biodegradable plastic materials, which justifies the technological development of new products. In this way, the present study presents itself as a bibliographic review about the application of different sources of starch in the production of biodegradable films using a casting technique to obtain the films. For this construction, a comparative analysis of 10 (ten) basic literature was used, dealing with different starch sources, but which used the casting technique in its preparation. The results showed that most of the reduced values of solubility for biofilms, indicating that these can be used in the protection of foods in which water activity is high. Regarding the effect of starch concentration on the thickness of biodegradable films, there is a direct relationship between thickness and the properties of the biofilms obtained, through non-homogeneity in most literature. In relation to water vapor permeability, this parameter was significantly influenced by the presence of the plasticizer. Specifically, glycerol, generated films with hydrophilic character and consequently with greater permeabilities. As for the effect of the additive on the properties of the sought biofilms, those with plasticizing action impacted more complete. The highlight was noticed, above all, in films impregnated with rosemary essential oil, which still has an antimicrobial effect on Salmonella sp. and Bacillus cereus, but they were characterized with high hydrophilicity, finding it a hindrance for their application as food packaging. The use of the Casting technique proved to be viable for the development of biodegradable films based on starch, but it still requires improvements and new studies to make it more accurate.